Hardware structures of hydronic systems for speed control. (August 2016) - Avram, M; Spânu, A; Bucşan, C; Besnea, D
Abstract: Most hydraulic actuating systems use constant flow pumps, for economic reasons. The resistive method is then used to control the speed of the actuated load. In the case of high performance systems the flow area is modified using analogical or numeric electric commands applied to proportional flow control devices. In the first part of the paper some hardware structures of hydronic actuating systems used for speed control are presented, and in the second part two experimental models of such systems are presented. Some aspects regarding the output improvement of such a system are also considered.